The Role of Servant Leadership in Enhancing Individual Innovativeness - Munir, Rosintansafinas; Noridan, Wafaa Syuhada; Hairuddin, Hanitahaiza (Advances in Social Sciences Research Journal, 2023)
It is undeniable that organizations today need to be more innovative in order to be sustained due to the increasingly competitive environment. Further, creative and innovative employees are crucial in supporting the organization to be more competitive. Unfortunately, the level of individual innovativeness in Malaysia remains at a moderate level. Thus, it is believed that the role of servant leadership is imperative to enhance the innovativeness among the staff in the organisations. This study aims to examine the influence of servant leadership’s characteristics, i.e. altruistic calling, emotional healing, and organizational stewardship in fostering individual innovativeness. A total of 177 administrative staff from private educational institutions in Selangor participated in the survey. The Partial Least Square (PLS) Structural Equation Modeling (SEM) (PLS-SEM) was applied in assessing the path modeling. The results indicated that altruistic calling, emotional healing, and organizational stewardship positively and significantly influenced the individual innovativeness. A well-practiced servant leadership in the organisation will lead the employees to be more creative and innovative. In addition, individual innovativeness can increase the innovative performance level of the organization. This study will serve as a guideline for the management to design new strategies in engaging leaders and employees to strive for innovation as well as to stimulate individual innovativeness.